Exploring the time-course and the reference frames of adaptation to optical prisms and its aftereffects. (August 2021) - Terruzzi, Stefano; Crivelli, Damiano; Campana, Elena; Pisoni, Alberto; Romero Lauro, Leonor J.; Bolognini, Nadia; Vallar, Giuseppe
Abstract: Prism adaptation (PA) is used to investigate visuo-motor plasticity and to rehabilitate the syndrome of Unilateral Spatial Neglect (USN). After PA, participants show aftereffects (AEs), contralateral to the side of the optical displacement in several tasks. This study explored the features of these AEs, specifically the "egocentric" versus "allocentric, object-based", reference frames involved, and their time course. In three experiments, healthy participants adapted to prismatic lenses inducing a horizontal displacement of the visual field. In Experiment #1, participants adapted to rightward displacing prisms. Four tasks were used requiring repeated pointings towards the participant's subjective egocentric straight-ahead, with the availability of proprioceptive or visual-proprioceptive signals, and, in some conditions, of an external allocentric visual frame (i.e., a rectangular paper sheet). Experiment #2 explored the role of the position of the allocentric frame, with AEs being tested by straight-ahead and frame bisection tasks, requiring pointing toward the external visual frame, placed in different positions of the working space. An egocentric visual proprioceptive task was administered after prism removal and after the execution of the allocentric tasks, to assess the effectiveness of the PA, as indexed by the AEs, and their persistence up to the end of the administration of the allocentric tasks. Experiment #3 differed from #2 in that participants adapted to leftward displacing lenses. Consistent with evidence from USN patients, in Experiment #1, in the egocentric tasks, AEs lasting up to 30 min after PA were found. In Experiment #2, AEs in "allocentric" tasks did not occur, regardless of frame position. Experiment #3 showed AEs in both the "egocentric" and the "allocentric" tasks, with the latter being minor in size. These findings illustrate that the spatial reference systems modulated by PA in extra-personal space primarily operate in spatial "egocentric" reference frames, with a comparatively minor and direction-specific role of "allocentric" frames.